THE EFFECT OF INFORMATION AND TECHNOLOGY (IT) BASED PARAGRAPH WRITING MATERIALS FOR STUDENTS' WRITING SKILLS IN PANDEMIC ERA - Sulistyahadi, Sulistyahadi; Hasbullah (Media Bina Ilmiah, 2023)
Nowadays almost technological facilities are owned by all students such as laptop or best HP multifunctional. The pandemic era forces human do all of the activities by using these media, this condition also forces the students and lecturer in the university to do teaching and learning process by using those media too. Mandating that the learning process begins to make technology as a learning medium that is able to create a conducive and wider atmosphere so that lecture learning is not limited by face to face activities and printed handbook but can use technology as a material development and learning process especially related to "paragraph writing" courses whose target is to make students able to write paragraphs well in pandemic era. In this case, this research has some purposes, they are developing teaching materials of information and technology-based "paragraph writing" (IT) courses; review how the effectiveness of IT-based "Paragraph Writing" teaching materials to improve student writing skills in pandemic era; and knowing the perception of students towards teaching materials developed based on Information and technology (IT) in pandemic era.